1997
DOI: 10.1182/blood.v90.1.346
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Acute Leukemia Cells to Cytarabine Is a Correlate of Cellular es Nucleoside Transporter Site Content Measured by Flow Cytometry With SAENTA-Fluorescein

Abstract: Cytarabine (araC) is converted to araC 5′-triphosphate after entering leukemia cells as a substrate for nucleoside transport processes. This study tested the relationship between araC cytotoxicity, measured in an in vitro tetrazolium dye reduction assay of cell viability, and the cellular abundance of es nucleoside transport elements, assayed by a flow cytometric method that used the es-specific stain, 5-(SAENTA-x8)-fluorescein (5-(Sx8)-F), in cultured leukemia cells and in myeloblasts and lymphoblasts (blasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…ENT‐mediated transport of nucleoside analogs is often the rate‐limiting step for drug‐induced cell cytotoxicity [6]. Thus, it is not surprising that studies have found a positive correlation between the expression of hENT1 and cancer cell sensitivity to the nucleoside analogs Ara‐C [19] and gemcitabine [20]. The reduction in hENT1 expression is a common mechanism for resistance to antimetabolite treatment of cancer [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…ENT‐mediated transport of nucleoside analogs is often the rate‐limiting step for drug‐induced cell cytotoxicity [6]. Thus, it is not surprising that studies have found a positive correlation between the expression of hENT1 and cancer cell sensitivity to the nucleoside analogs Ara‐C [19] and gemcitabine [20]. The reduction in hENT1 expression is a common mechanism for resistance to antimetabolite treatment of cancer [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…This was done mostly in lymphoproliferative malignancies, as these diseases allow the simultaneous measurement of the ex vivo sensitivity to drugs used in patient therapy. Several studies have reported a correlation between hENT1 expression and cytarabine sensitivity in acute myeloid and lymphoid leukaemia (AML and ALL) [81][82][83]. In chronic lymphocitic leukaemia (CLL) a significant correlation between fludarabine uptake via ENT carriers, hENT2 protein expression and ex vivo sensitivity was detected [78,84].…”
Section: Anticancer and Antiviral Drugsmentioning
confidence: 99%
“…Sensitivity to Ara‐C in infant ALL appeared not to be associated with rearrangements of the MLL gene, as both MLL rearranged and MLL germ line infant ALL cases appeared equally sensitive to this drug in vitro (Stam et al , 2005). The remarkable sensitivity to Ara‐C seems most likely to be due to the elevated expression of the human equilibrative nucleoside transporter 1 (hENT1) (Stam et al , 2003), on which Ara‐C is mainly dependent to permeate the cell membrane (Wiley et al , 1982; White et al , 1987; Gati et al , 1997). However, at high‐dose Ara‐C regimens generating high extracellular drug concentrations, Ara‐C also enters the cell by passive diffusion and membrane transport via ENT1 is circumvented.…”
Section: Nucleoside Analogue Sensitivity and Therapeutic Possibilitiementioning
confidence: 99%